2020
DOI: 10.1002/aenm.201903785
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Reversible Oxygen Redox Chemistry in Layered Oxides for Sodium‐Ion Batteries

Abstract: premise of guaranteeing electrochemical stability upon cycling. [2] Not rigidly limited to conventional redox reactions based on transition metal (TM) centers, redox activity centered at the oxide anions is emergently viewed as a promising strategy to effectively increase the energy density of SIBs. [3] When conventional cationic and novel anionic activities are triggered simultaneously, several cathodes delivering boosted capacities break the shackle of reversible TM redox couples. [4] As a representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
123
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 56 publications
(30 reference statements)
2
123
0
Order By: Relevance
“…Therefore, it is concluded that the average oxidation state of Ru may vary from 4+ to 5+ depending on structure and chemical composition, and Ru can be electroactive and nonelectroactive regardless of its initial oxidation state (Table S2, Supporting Information). [34,42,43,[46][47][48][49] Turning to the oxygen redox activity in this material, the O K-edge spectrum was measured and XPS analysis was performed for Na[Ni 2 ). In addition, the peroxo-related peak was still visible during discharge to 3 V and disappeared at 2 V, meaning that the oxidized lattice oxygen was reduced to O 2− in the Na[Ni 2/3 Ru 1/3 ]O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is concluded that the average oxidation state of Ru may vary from 4+ to 5+ depending on structure and chemical composition, and Ru can be electroactive and nonelectroactive regardless of its initial oxidation state (Table S2, Supporting Information). [34,42,43,[46][47][48][49] Turning to the oxygen redox activity in this material, the O K-edge spectrum was measured and XPS analysis was performed for Na[Ni 2 ). In addition, the peroxo-related peak was still visible during discharge to 3 V and disappeared at 2 V, meaning that the oxidized lattice oxygen was reduced to O 2− in the Na[Ni 2/3 Ru 1/3 ]O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[22] For SIBs, the anionic redox reaction is available for not only Na-rich materials but also Na-deficient P2/P3-type compounds. [23][24][25][26][27][28][29][30][31][32][33][34][35] For example, manganese-based P2-type sodiumdeficient materials with low-valence substituents, such as Li, [26,30,31] Zn, [23,29] and Mg, [27,28] have demonstrated oxygenredox activity with good structural stability. It is generally accepted that a NaOA (A = Li, Na, Mg, Zn, or vacancy) local coordination environment is the essential requirement for oxygen redox activation in P2/O3 type layered Na x [ATM] O 2 (TM: transition metals).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] However, the irreversible loss of lattice oxygen inevitably triggers undesirable migration of TM and structure distortion when cycling, leading to a capacity decay with faded output potential. [ 3 ] Meanwhile, the highly reactive Ni 4+ produced at high voltage would induce parasitic side reactions (SR) at the interface of electrode/electrolyte, generating cathode electrolyte interphase (CEI) derived from the electrolyte decomposition, TM migration and dissolution. [ 4 ] The SR, coupled with the irreversible oxygen loss, further induces the capacity loss and voltage fading.…”
Section: Introductionmentioning
confidence: 99%
“…The powder X‐ray diffraction (PXRD) and inductively coupled plasma (ICP, Table S3) were collected to characterize the crystal structure of the as‐synthesized P2‐NLAMO (Figure 2A). All the diffraction peaks of P2‐NLAMO are highly consistent with typical P2 phase (space group: P6 3 /mmc) 24‐27 . The crystal structure of P2‐NLAMO was further verified by XRD Rietveld refinement.…”
Section: Resultsmentioning
confidence: 60%